Analytical study of mandible: Prerequisite for sex determination - Bhagya Shree; Sachin Soni; Sanjay K Sharma; Keshav Handge; Ashwini Kumar; Sushant S Das; Nidhi Puri (Journal of Pharmacy and Bioallied Sciences, 2023)
Background: Human skull consists of various bones. One of them is mandible which is quite resistant, tough and shows systemic differences in form between individuals of different sex. It resists putrefaction also. There are characteristic features in the mandible that help us to differentiate sex in case of unknown victims like in mass disasters or in case fragmentary remains of the skeleton are found. Analysis of mandible with regard to its features is of great assistance in the determination of sex. Materials and Methods: A total of 80 dry mandible bones were collected. Morphological and morphometric parameters were studied to determine their sex. A total of nine parameters, i.e., three non-metric and six metric parameters were observed for each mandible. Data was collected for each parameter. Results: Among 80 dry mandible bones, 55 were males and 25 were females. 81.2% males bones had a square chin whereas, 80% females had a rounded chin. Gonial flare was everted in 89% males and inverted in 68% females. Conclusion: Mandible exhibits significant sexual differences. Various morphological and morphometric parameters are essential for sex determination in case of mandible bone.